2003
DOI: 10.1177/000313480306901111
|View full text |Cite
|
Sign up to set email alerts
|

What Predicts Serious Complications in Colorectal Cancer Resection?

Abstract: Virtually all volume-outcome studies use mortality as their outcome measure, yet most general surgical procedures have low in-patient death rates. We examined whether hospital surgical volume impacts other colorectal cancer resection outcomes and complications. Colorectal cancer (CRC) resections from 1996 to 2000 were identified using the California hospital discharge database. Comorbidity was graded using a modified Charlson index. Hospital CRC resection volume was calculated. Serious medical complications we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(2 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…While most risk prediction models focus on mortality risks (14, 15) and surgical complications (16)(17)(18)(19), few studies have evaluated the potential loss of functional independence among older survivors of cancer, including survivors of CRC. Previous studies conducted during and after cancer treatment have found associations between sociodemographic, health, and clinical factors with poor health and poor disability status among cancer patients, including those diagnosed with CRC (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…While most risk prediction models focus on mortality risks (14, 15) and surgical complications (16)(17)(18)(19), few studies have evaluated the potential loss of functional independence among older survivors of cancer, including survivors of CRC. Previous studies conducted during and after cancer treatment have found associations between sociodemographic, health, and clinical factors with poor health and poor disability status among cancer patients, including those diagnosed with CRC (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…While most risk prediction models focus on mortality risks (Dasgupta et al, 2013;Friedenreich et al, 2020) and surgical complications (Zingmond et al, 2003;Nakanishi et al, 2018;Pak et al, 2020;Souwer et al, 2021), few studies have evaluated the potential loss of functional independence among older survivors of cancer, including survivors of CRC. Previous studies conducted during and after cancer treatment have found associations between sociodemographic, health, and clinical factors with poor health and disability status among cancer patients, including those diagnosed with CRC (Hewitt et al, 2003;Green et al, 2011;Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%